Life in a State of Limbo – Narratives of Place, Health, and Integration Among Later Life Female Migrants in Sweden - Magnusson, Finnur (Socialinė teorija, empirija, politika ir praktika, 2024)
International migration is a prioritized domain of European aging research. Using a qualitative approach, the author has gathered accounts among Iranian later-life females in the Swedish city of Malmö, suffering from social isolation. The women in this article found themselves in a situation like that of other later-life migrants in Sweden. Several studies have shown how these groups are at risk of ending up in a social isolation which can be hard to break. The situation of the later-life migrant women discussed in this study is characterized by the loss of numerous deep-seated and natural social bonds connected to ethnicity, family, language, and culture. To cope with their exposed situation, the local Iranian-Swedish association provided some self-arranged activities, offering opportunities to social integration. The aim of the study is to demonstrate how the women described their life situation where a local day center made up the key foundation of their social life in  a Swedish city in 2000–2008. Typical of that period was that solutions of the alarming situation of some foreign-born elderly citizens were discussed by local authorities, as well as volunteer organizations. Thus, the aim is not to describe the present situation among later life migrants. On the contrary, the perspective is retrospective. The theoretical inspirations used in the article derive from a broader backdrop of social-constructive assumptions that define narratives or accounts as explanations of the reality of everyday life and experiences. In the article the women’s stories are defined as small, local, erratic narratives, nevertheless explaining the reality of everyday life and experiences which in their turn reflect the state of illness, locally specific attachment and social isolation. Three salient themes emerge in the material: place bound experiences, illness and unsuccessful integration. The narratives are defined as small irregular accounts, contrasting larger narratives of later-life migration. The article shows how the women depicted their situation as a borderline between an Iranian life in exile and a Swedish society, leaving them in a state of Limbo. The women expressed ambitions of integrate into a Swedish community of senior citizens, providing privileges and civil rights. Thus, the narratives challenge common generalizing images of later-life migrants and their life conditions.